Analisis Pemikiran Hermeneutika Hadis Yusuf Al-Qardhawi - Muhammad Zainul Hasan (Al Irfani: Journal of Al Qur'anic and Tafsir, 2020)
In order to obtain a good and comprehensive understanding of hadith with the intention of avoiding a textual and not grounded understanding Yusuf al-Qardhawi offers a solutive concept and methodology in understanding the Prophet's hadith. This research is a study of literature, especially examining the method of understanding hadiths offered by al-Qardhawi in Kaifa Nata'amalu Ma'a As-Sunnah An-Nabawiyyah. In addition, researchers also used other literature as a complementary addition. The method of analysis used in this study is hermeneutic analysis, in which researchers describe objects that are systematically reviewed and then analyzed with a hermeneutic approach. Come to the conclusion that the most important point we get from the offer given by al-Qardhawi is how we understand and realize while relive the hadith of the Prophet who shalih likulli zaman wa makan. What al-Qardhawi has offered in understanding the Prophet's hadith with the points mentioned in this study is a form of hermeneutic work, although al-Qardhawi does not directly demonstrate his method as an offer of hermeneutic methods.